PSEUDOATHETOSIS AS A PRESENTING SYMPTOM OF CNS DEMYELINATION. (29th November 2012) - Pegg, E; Chhetri, SK; Zaidi, S; Mathur, S; Majeed, T
Abstract : Pseudoathetosis refers to a movement disorder characterised by involuntary, slow, writhing movements resulting from loss of proprioception. We report a case of pseudoathetosis secondary to a demyelinating lesion in the cervical spinal cord. A 27-year-old lady presented with a 1 week history of paraesthesias in her left hand. Within the next few days, the left hand felt clumsy. Past medical history was unremarkable. Clinical examination demonstrated slow, continuous, pseudoathetoid movements involving fingers of both hands, more on the left, and worsened by eye closure. Vibration and joint position sense were impaired in the left upper limb up to the elbow. Joint position sense was mildly impaired in the right fingers. Finger to nose test was impaired on the left upper limb, particularly with eye closure. The rest of the neurological examination was unremarkable. Investigations including infective, metabolic and inflammatory screens were normal. Oligoclonal bands were present in the cerebrospinal fluid. MR brain showed a solitary focus of high signal near the occipital horn of the right lateral ventricle. Cervical spine MRI showed mildly enhancing T2 high signal change in the spinal cord at C3 and C4 levels (figure 1). She was treated with a 3 day course of intravenous methylprednisolone. Follow up assessment at 2 months revealed complete resolution of her symptoms. Pseudoathetosis can occur with lesions located at any level of the sensory pathways from peripheral sensory nerves to the parietal cortex and may be a presenting symptom of CNS demyelination.